ANALISIS KEKUATAN FRAME SEPEDA LISTRIK NGEBUTS MENGGUNAKAN METODE ELEMEN HINGGA - Fadhli Dzil Ikram; Erik Erik (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2022)
Three hundred and ten million people are affected by global climate change caused by carbon dioxide gas. The internal combustion engine that dominates the transportation fleet is one of the contributors to the amount of carbon dioxide in the atmosphere. Research related to environmentally friendly vehicles, in this case, electric vehicles, needs to continue to be carried out followed by downstream research results in the industry. The hope is to reduce the amount of greenhouse gas emissions produced by internal combustion engine vehicles. This study aims to determine the strength of the electric bicycle frame by conducting a stress analysis using the finite element method. The geometry modeling, inputs (data of material properties, geometry, loads, boundary conditions), mesh, solve, and validation are the steps that are passed in this research. The results show that the maximum equivalent stress (von Mises) of 98.31 MPa occurs at the joint between the Seat Tube and Seat Stay, while the minimum stress of 0.01 MPa occurs at the top of the Head Tube. The maximum deformation that occurs at the top of the Seat Tube is 0.15 mm. The minimum safety factor value on the frame is 2.39. Based on this value, the electric bicycle frame can be said to be strong enough to withstand the load of the rider and the battery.